PENGARUH PELATIHAN, PEMBINAAN DAN MOTIVASI TERHADAP KINERJA PELAKU USAHA MIKRO KECIL MENENGAH (UMKM) MELALUI KOMPETENSI SEBAGAI VARIABEL INTERVENING PADA KOTA SORONG - Yance Jitmau; Meithiana Indrasari (Bajang Institute, 2025)
MSMEs experience various business development problems due to entrepreneurial competencies that are not yet superior, especially technical skills and managerial abilities. This is often caused because HR in small-scale businesses still rely on the owner or one particular person, who finds it difficult to trust others to help with their business activities. The purpose of this study is to analyze the effect of Training, Coaching, Motivation on performance through Competence in MSME actors in Sorong Regency. This type of research is causal research with a quantitative research approach. The data collection technique uses questionnaires. The population in this study were 125 MSME actors in Sorong Regency. This study used questionnaires in data collection and was analyzed using SEM PLS. The results of the study stated that Training, Coaching and Motivation had a significant effect on the Competence of MSME actors in Sorong Regency. Coaching and Competence had a significant effect on the Performance of MSME actors in Sorong Regency. However, Training and Motivation had no significant effect on the Performance of MSME actors in Sorong Regency. Competence was able to mediate the relationship between Training, Coaching and Motivation on the Performance of MSME actors in Sorong Regency